A Simulation Model of Global Pension Investment - MacKellar, Landis (OECD Publishing, 1998)
How and to what extent can a high degree of global financial integration help the fast-ageing OECD benefit from the delayed ageing process in the non-OECD area? The question is being raised with increasing urgency as it is slowly understood that even fully funded pension schemes will not escape demographic pressures in the absence of considerable capital flows between the ageing OECD and the younger part of the world. A simulation with a two-region neo-classical economic-demographic model reaches two basic conclusions of importance to policy makers. First, capital flows from fast-ageing, mostly OECD countries to slowly ageing, mostly developing countries can only slightly attenuate, but not reverse, the consequences of an ageing population on falling returns to capital. Second, significant distributional effects are likely to arise from the interaction of population ageing and financial integration. Global financial integration benefits elderly lifetime savers, but hurts elderly ...
Keywords: Development